Variability of Soil Infiltration under 15 Year Old Plantation in Jabalpur, Central India - Verma, Manisha; Sahu, M. L. (Indian Forester, 2017)
Rainwater harvesting is the only solution to combat water crises problems of 21st century. Trees are vital to control heavy rainfall and ground water recharge due to its impact on soil infiltration characteristics. Rain water harvesting potential of trees can be explored by standard methods of infiltration tests. Infiltration tests were carried out under the 15 years old plantations of Dalbergia sissoo, Tectona grandis and Terminalia arjuna tree species and grassland. The steady state (7 hr duration) infiltration rate was significantly higher under T.grandis (45 mm hr ) followed by D.sissoo (18 mm-1 hr-1), T.arjuna (8 mm-1 hr-1) and grassland (5 mm hr ). Similarly cumulative depth of water recharged in 7 hours was significantly higher in T.grandis (315 mm) followed by D.sissoo (128 mm), T.arjuna (55 mm) and grassland (34 mm). Among the investigated tree species Tectona grandis was found very much suitable for rain water harvesting.